2018
DOI: 10.1097/mej.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective validation of the pulmonary embolism rule-out criteria rule in ‘PE unlikely’ patients with suspected pulmonary embolism

Abstract: The PERC rule has a high negative predictive value for excluding PE in patients presenting with suspected PE to the ED. However, the PERC rule may still miss around 8% of confirmed PE in patients who are deemed 'PE unlikely' by a dichotomized Wells score. Caution is advised in using the PERC rule as a substitute for the standard D-dimer test in all these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…These data suggests that PERC should be utilized in the emergency department. Prior to this aforementioned randomised controlled trial for the PERC rule, a 2016 study demonstrated that although PERC had a high negative predictive value for excluding PE, it may miss around 8% of confirmed PE and caution was advised to its utilization [18]. We hope the subsequent multi-centre randomised controlled trial helps to alleviate these concerns.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggests that PERC should be utilized in the emergency department. Prior to this aforementioned randomised controlled trial for the PERC rule, a 2016 study demonstrated that although PERC had a high negative predictive value for excluding PE, it may miss around 8% of confirmed PE and caution was advised to its utilization [18]. We hope the subsequent multi-centre randomised controlled trial helps to alleviate these concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomised clinical trial including 1916 patients with suspected PE, considered by clinical judgement (holistically) to be at very low risk for PE, the use of the pulmonary embolism rule-out criteria (PERC) safely excluded PE [48]. The PERC strategy may reduce the number of d -dimer tests in patients with very low clinical probability of PE [48], although caution is advised in using the PERC rule [49].…”
Section: Pulmonary Embolismmentioning
confidence: 99%
“…However, despite high negative predictive value, approximately 8% of confirmed PEs are missed in patients with a low Wells score [15].…”
Section: Resultsmentioning
confidence: 99%